The Role of Teachers’ Reading Habits and Perception about EFL Reading Towards Students’ Literacy - Yohanes Eugnasius Nai; Anselmus Sahan; Delti Yulita (ELT Worldwide: Journal of English Language Teaching, 2022)
The purpose of this study was to find out how teacher’s reading habits and perception affect students’ literacy. Firstly, the researcher investigated teacher’s reading habits by using Iftanti (2012) questionnaire about reading habits. It is found that teachers have very limited reading habits per day and they didn’t have solid reading habits even they have studied and read English text since junior high school and senior high school. Moreover, teachers’ notion about reading is changing along with the development of technology where teachers tend to find reading source from Internet and read through smartphone rather than books. Secondly, the researcher investigated students’ literacy about interview students’ reading habit at school and home and gave test to measure their ability to comprehend the text. It was found that students’ literacy was low due to their lack of time on extensive reading. Based on the result, it is concluded that teachers’ reading habits gives significant effect on students’ literacy. Teachers hold an important role to build a solid reading habits to increase students’ literacy, specifically in EFL reading. Thus, in order to build that good reading habits, teachers must have their own good reading habits. Teachers need to consistently increase their reading time on daily basis and starts to collect many sources of reading.